Responsibility Accounting's Influence on Corporate Governance: Insights from Iraq Private Banks - Hassan, Mohammed Ali; Abdulabass, Ahmed Abdulkadhum; salman , Rafid mohammed; Jaffar , Zaid Abdulzahra (Journal of Accounting Science, 2024)
General Background: The study explores the influence of responsibility accounting on corporate governance within Iraqi private banks, a subject vital for ensuring effective management and transparency. Specific Background: Despite the growing importance of corporate governance in mitigating financial crises, the role of responsibility accounting in enhancing governance practices remains underexplored, particularly in developing economies. Knowledge Gap: There exists a paucity of research on how responsibility accounting can operationalize corporate governance principles in the context of Iraq’s banking sector. Aims: This research aims to assess the impact of responsibility accounting systems on the governance structures of selected Iraqi private banks listed on the Iraq Stock Exchange. Results: The study found a statistically significant positive correlation between responsibility accounting and corporate governance, indicating that banks with robust responsibility accounting systems exhibit enhanced governance practices. Novelty: This study provides empirical evidence on the effectiveness of responsibility accounting in improving corporate governance, highlighting its potential to bridge existing gaps in governance frameworks in emerging markets. Implications: The findings suggest that adopting comprehensive responsibility accounting practices can significantly enhance corporate governance, thereby offering strategic insights for policymakers and bank executives aiming to strengthen governance mechanisms in the banking sector.